Transcriptional Correlates of Chronic Alcohol Neuroadaptation in Drosophila Larvae - Anqueira-González, Amanda; Acevedo-Gonzalez, Jenny P.; Montes-Mercado, Airined; Irizarry-Hernández, Claudia; Fuenzalida-Uribe, Nicolás L.; Ghezzi, Alfredo (Frontiers in Behavioral Neuroscience, 2021)
When presented with the choice, Drosophila melanogaster females will often prefer to lay eggs on food containing a significant amount of alcohol. While, in some cases, this behavioral decision can provide a survival advantage to the developing larvae, it can also lead to developmental and cognitive problems. Alcohol consumption can affect executive functions, episodic memory, and other brain function capacities. However, in the fruit fly, the initial cognitive effects of alcohol consumption have been shown to reverse upon persistent exposure to alcohol. Using an olfactory conditioning assay where an odorant is implemented as a conditioned stimulus and paired with a heat shock as an unconditioned stimulus, a previous study has shown that when exposed to a short acute dose of alcohol, Drosophila larvae can no longer learn this association. Interestingly, upon prolonged chronic alcohol exposure, larvae seem to successfully avoid the conditioned stimulus just as well as control alcohol-naive larvae, suggestive of alcohol-induced neuroadaptations. However, the mechanisms by which Drosophila adapt to the presence of alcohol remains unknown. In this study, we explore the transcriptional correlates of neuroadaptation in Drosophila larvae exposed to chronic alcohol to understand the genetic and cellular components responsible for this adaptation. For this, we employed RNA sequencing technology to evaluate differences in gene expression in the brain of larvae chronically exposed to alcohol. Our results suggest that alcohol-induced neuroadaptations are modulated by a diverse array of synaptic genes within the larval brain through a series of epigenetic modulators.